Legal aid is now provided at the expense of the state! - Ra’no Tojimurodova (Journal of Contemporary Business Law & Technology: Cyber Law, Blockchain, and Legal Innovations, 2024)
In Uzbekistan, measures are being taken to ensure the rights and legal interests of citizens, to build a comfortable life for them, and to strengthen all this through legislation. This article examines to whom and when public legal aid is provided